Karsinogenesis Kanker Kolorektal, Hubungannya dengan Diet dan Mikroflora Usus - Ernawaty Tamba (Jurnal Kedokteran Meditek, 2012)
Abstrackcolorectual cancer is a type of cancer that exists in the colon and rectum. In Indonesia, the number of patients who suffer the disease under the age of 40 years old, rose up until 35.26% and placed in the rank of 10th. In the highly advanced country. the disease climbs sharply as the patient with age more than 50 years old, only 3% less compared to the patient less than 40 years old. Colorectal cancer has become the 2nd most frequent disease that causing death at the end. Diet has also become one of the significant factor that may cause the cancer. The diet mechanism goes to be one of the etiology of colorectal cancer, which actually still undiscovered. For individuals who had high opprtunity for colorectal cancer to be exist, there are significant alteration in the feces’ microflora. Diet gives huge role with the changes in the microflora’s activity, which reflected in the changes of enzyme’s activities.Key words : colorectal cancer, microflora, enzyme’s activities